The role of sport infrastructure: use, preferences and needs - Nagy , Adrián; Tobak , Júlia (Applied Studies in Agribusiness and Commerce, 2015)
Leisure and mass sports are very significant both socially and economically. Physical activities contribute to forming a healthier society. Skills and abilities developed by sport promote people’s well-being and directly improve their physical, mental and psychological performance this way producing better quality of life. The state of health of the workforce is a more and more frequent question in developed and developing economies but mostly in the western civilizations. Researches prove that those who are more active phisicly can perform better at their work and are more efficient in their jobs. They claim less sick leave benefit and their health insurance costs are lower, this way preserving the health of the workforce can be an investment in the future. If we want the population to live in a healthier way and do more sports only education and motivation are not enough, it is very important to provide the appropriate infrastructural background as well. People can have a wide range of choice provided by the local sports establishments and companies and the possibilities resulting from sport infrastructure investments. The effects of sport infrastructure investments and developements are many folded and long-therm, but it is worth approaching their benefits from different points of view. Researching this topic can contribute to better understanding of the society from the points of view of health care, economy and sociology. The aim of our work was to examine the sporting habits and sports consumption. In order to get to know the consumers we carried out a survey with 350 particiant with the help of an online questionnaire. When analyzing it I focused on the answers given by those who were active in sports, which was the 75% of total sample. In the analysis of the answers and relations between the questions and the different factors we used the SPSS Statistics program. Providing sport establishments and facilities and initiating such investments are highly important for each region. From the answers of the quesstionned we can learn what facilities are available for the consumers and what they miss most in the living area. JEL code: L83